2006
DOI: 10.1111/j.1469-0691.2006.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

The possible significance of Clostridium spp. in blood cultures

Abstract: The significance of Clostridium spp. in blood cultures was evaluated by two methods. In the first part of the study, a group of 80 patients with Clostridium spp. bacteraemia was compared with a group of 100 patients with Bacillus spp. in blood cultures, making the assumption that Bacillus almost invariably represents contamination (pseudobacteraemia). Significant differences were found between the two groups, suggesting that growth of Clostridium did not represent pseudobacteraemia. Patients with Clostridium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…15,38 However, several more recent investigations have demonstrated that Clostridium species are usually pathogenic and that failure to institute appropriate antimicrobial therapy is associated with an adverse mortality outcome. 5,39 Thus, our rates of bacteremia reported in this study likely overestimate to at least some degree the true incidence of clinically significant clostridial bloodstream infections. A second limitation of our study is that we used hospital discharge coding data to identify clinical details and did not access individual patient charts.…”
Section: Discussionmentioning
confidence: 68%
“…15,38 However, several more recent investigations have demonstrated that Clostridium species are usually pathogenic and that failure to institute appropriate antimicrobial therapy is associated with an adverse mortality outcome. 5,39 Thus, our rates of bacteremia reported in this study likely overestimate to at least some degree the true incidence of clinically significant clostridial bloodstream infections. A second limitation of our study is that we used hospital discharge coding data to identify clinical details and did not access individual patient charts.…”
Section: Discussionmentioning
confidence: 68%
“…20 In human medicine, organism identification is considered one of the primary factors in clinical discrimination between true causes of bacteremia and contamination of blood submitted for bacteriologic culture. However, unlike human medicine, where clostridial species have been documented as causative pathogens in true bacteremia in the hospitalized adult population and some debate exists as the to the clinical importance of a positive culture result, 21 to the authors' knowledge, there are no reports of a clostridial species implicated in bacteremia of an immunocompetent adult horse. Although the presence of the gas stippling during the initial ultrasonographic examination and aspiration of fetid fluid from the abscess on day 21 supported an anaerobic infection, unfortunately, culture of anaerobic organisms from the fetid abscess fluid or from the necrotic hepatic tissue was not successful.…”
Section: Discussionmentioning
confidence: 98%
“…Findings on CBC revealed leukopenia with a marked neutropenia and a left shift with moderate toxic changes. Serum biochemical analysis revealed marked hyperfibrinogenemia, hypoalbuminemia, hyperglobulinemia, and mildly high serum amyloid A concentration (Table 1; day21). Initial abdominal ultrasonography at the time of hospital readmission revealed a return of the marked hepatic parenchymal abnormalities in the region of the left lateral liver lobe.…”
mentioning
confidence: 99%
“…are also found as normal inhabitants of the human colon and may similarly cause bacteremic disease in patients with perturbed host defense mechanisms (22). Polymicrobial bacteremia is frequently observed in patients with Clostridium bloodstream infections, particularly in the setting of severe sepsis or septic shock (2,21,22,25), whereby Clostridium spp. and infectious agents such as Enterococcus spp.…”
mentioning
confidence: 99%
“…Severe sepsis or septic shock occurs in approximately 40% of patients with Clostridium bacteremia and, in this setting, is associated with a mortality rate of over 50% (3). Patients with hematological malignancies, particularly those experiencing partial failure of chemotherapy, have been shown to be at increased risk for Clostridium bacteremia, with or without sepsis or septic shock (2,3,25). The rigorous chemotherapeutic regimens used for the treatment of hematological malignancies are typically associated with damage to the mucosa of the gastrointestinal tract, leading to potential translocation of anaerobic bacteria such as Clostridium spp.…”
mentioning
confidence: 99%